Adaptation, optimisation and simulation of the CSMA/CA protocol for a low earth orbit satellite UHF link - Cawood, Andrew Dudley (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.